2014
DOI: 10.5114/wo.2014.40598
|View full text |Cite
|
Sign up to set email alerts
|

De novo malignant eccrine spiradenoma and metachronous lung cancer

Abstract: Malignant eccrine spiradenoma is an extremely rare sweat-gland tumour. Herein we aimed to present an 81-yearold woman with malignant eccrine spiradenoma repeated on the thigh and metachronous lung cancer. She presented with a palpable swelling in the right thigh region. Her systemic screening was normal and excisional biopsy was performed. A diagnosis of malignant eccrine spiradenoma was made. Thirty-two months later, the tumour recurred in the same region. The tumour was excised again. Lymph node metastasis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…25,87 All of the cases with margins of <1 cm, on the other hand, reported distant metastases, while two patients died. 1,38,77,79,86 The mean time to local recurrence or metastasis after initial therapy was 20.1 months (range 0-192 months). Approximately, 75% of these were detected in the first 12 months of follow up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25,87 All of the cases with margins of <1 cm, on the other hand, reported distant metastases, while two patients died. 1,38,77,79,86 The mean time to local recurrence or metastasis after initial therapy was 20.1 months (range 0-192 months). Approximately, 75% of these were detected in the first 12 months of follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography was the preferred modality, used in 49.1% of these cases, followed by magnetic resonance imaging (MRI) (32.7%), X-ray (30.9%), bone scan (23.6%), ultrasound (20%), positron emission tomography (PET)/computed tomography (CT) (14.5%) and finally mammography (10.9%). [4][5][6][8][9][10][11][54][55][56][57][58][60][61][62][63][67][68][69][73][74][75][77][78][79] Staiger et al have recently recommended that patients presenting with confirmed malignant spiradenoma be evaluated with an MRI and fluorodeoxyglucose (FDG)-PET/CT. 74 Details regarding a fineneedle aspirate or punch biopsy was provided for 76 case reports and case series, representing 86 (61.9%) cases.…”
Section: Investigationsmentioning
confidence: 99%
See 1 more Smart Citation